2013
DOI: 10.1021/es304669p
|View full text |Cite
|
Sign up to set email alerts
|

Selective Chlorination of Natural Organic Matter: Identification of Previously Unknown Disinfection Byproducts

Abstract: Natural organic matter (NOM) serve as precursors for disinfection byproducts (DBPs) in drinking water production making NOM removal essential in predisinfection treatment processes. We identified molecular formulas of chlorinated DBPs after chlorination and chloramination in four Swedish surface water treatment plants (WTPs) using ultrahigh resolution Fourier transform ion cyclotron resonance mass spectrometry (FT-ICR-MS). Chlorine-containing formulas were detected before and after disinfection and were theref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
173
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(186 citation statements)
references
References 46 publications
10
173
2
1
Order By: Relevance
“…Among the 74 formulas of chlorine-containing organic components, 63 overlapped with the "already present" chlorine-containing formulas listed in the drinking water DBPs study by Lavonen et al 20 Lavonen and colleagues developed a classification method for differentiating formulas of chlorine-containing DBPs from "already present" chlorine-containing formulas (which are present before disinfection). 20 They suggested that the "already present" chlorine-containing formulas should not be considered as DBPs. However, in this study we observed that, compared to the SRFA control sample, the peak intensities of the already present chlorine-containing components increased 4 to 18 times after chlorination (Supporting Information, Figure S1, S2).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the 74 formulas of chlorine-containing organic components, 63 overlapped with the "already present" chlorine-containing formulas listed in the drinking water DBPs study by Lavonen et al 20 Lavonen and colleagues developed a classification method for differentiating formulas of chlorine-containing DBPs from "already present" chlorine-containing formulas (which are present before disinfection). 20 They suggested that the "already present" chlorine-containing formulas should not be considered as DBPs. However, in this study we observed that, compared to the SRFA control sample, the peak intensities of the already present chlorine-containing components increased 4 to 18 times after chlorination (Supporting Information, Figure S1, S2).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…12,13,20 The ultrahigh resolution and mass accuracy of FT-ICR MS provides molecular masses accurate to within 1 ppm, which often enables the determination of molecular formulas by mass measurement alone. 14,15,21 In our previous studies, molecular formulas of chlorine-containing DBPs have been identified with negative ion electrospray ionization (ESI) FT-ICR MS in both artificial and actual drinking water samples.…”
Section: ■ Introductionmentioning
confidence: 99%
“…However, the unit mass resolution of tqMS is still too low to allow nominally isobaric ions to be massresolved and may bias the compositional interpretation of I-DBPs. Recently, ultrahigh resolution Fourier transform ion cyclotron resonance mass spectrometry (FT-ICR MS) has been successfully used to characterize the previously unknown Cl-DBPs and Br-DBPs (Zhang et al, 2012a;Zhang et al, 2012b;Lavonen et al, 2013;Zhang et al, 2014). The ultrahigh resolution and mass accuracy of FT-ICR MS combined with electrospray ionization (ESI) allows the determination of unambiguous and exact molecular formulas (Stenson et al, 2003;Kim et al, 2006aKim et al, , 2006bHertkorn et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have reported that NOM may affect the toxicity of nanoparticles by forming NOM-nanoparticle composites [1], may interact with inorganic contaminant in the environment to affect its environmental behavior [2], and may be a source of new contaminants during the chlorination processes of drinking water [3,4]. Because NOM molecules play a pivotal role in the cycling and transport of elements in the ecosphere and have other effects on the environmental quality, it is important for environmental chemists to better understand the molecular composition and transformation of NOM.…”
Section: Introductionmentioning
confidence: 99%